Reforms and economic growth in transition economies: Complementarity, sequencing and speed - Karsten Staehr (Bank of Finland, Institute for Economies in Transition (BOFIT), 2003)
Growth regressions have provided important insights into the impact of economic reforms on growth in transition economies.Using principal components to decompose reform variables and construct reform clusters, we address unsettled issues such as the importance of sequencing and reform speed.The results indicate a broad-based reform policy is good for growth, but so is a policy of liberalisation and small-scale privatisation without structural reforms.Conversely, large-scale privatisation without adjoining reforms, market opening without supporting reforms and bank liberalisation without enterprise restructuring affect growth negatively.Swift reform policies allow transition countries to benefit from higher growth for a longer period of time.The speed of reforms otherwise appears to have only limited effects on short-term and medium-term growth.
URN:NBN:fi:bof-201408072165
Keywords: P21; P30; C33; H11; 330; Economic reforms; growth; principal components; gradualism versus big-bang